Leadership Ideas of Ridwan Kamil: A Conceptual Analysis - Haboddin, Muhtar (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2025)
This paper aims to explain Ridwan Kamil's idea of leadership. The choice of leadership ideas is based on the consideration that there has been no writing that specifically addresses this theme. This emptiness of the theme is the entrance to understanding Ridwan Kamil's idea of leadership in a fundamental way. Why leadership? Because leadership is one of the cores in government studies. In uncovering Ridwan Kamil's leadership ideas, there are two methods of data collection that are used in parallel, namely interviews and literature reviews. The results found that Ridwan Kamil's leadership ideas are very interesting, when defining the meaning of leadership. For example, leadership takes the risk of solving problems or providing real solutions for society. Furthermore, Ridwan Kamil also classified three levels of leadership starting from oneself, household, and community. In line with that, leaders must also mobilize their people. Furthermore, this article ends by critically assessing Ridwan Kamil's leadership ideas.